PENGGUNAAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA WORDWALL PADA MATERI SEPERTI APAKAH BUDAYA DAERAHKU UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V SD INPRES TARUS 1 KABUPATEN KUPANG - Yoseph Mariano Hendrawan Neparian; Maxsel Koro; Treesly Y. N. Adoe (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Thesis by Yoseph Mariano Hendrawan Neparian NIM 2001140179 with the title “The Use of Problem Based Learning Model Assisted by Wordwall Media on Material Like What is My Regional Culture to Improve Learning Outcomes of Grade V Students of SD Inpres Tarus 1 Kupang Regency.” The problem in this study is how to improve the learning outcomes of Vc grade students SD Inpres Tarus 1 through the application of problem based learning models assisted by wordwall media on material such as what is my regional culture with the aim of knowing the improvement of learning outcomes of Vc grade students of SD Inpres Tarus 1 through the application of problem based learning models assisted by wordwall media on material such as what is my regional culture. The location of this research was at SD Inpres Tarus 1, Kupang Regency. The research method used was classroom action research (PTK) which was carried out in two cycles. Each of them consists of planning, implementation, observation, and reflection stages. The research subjects were students of class Vc SD Inpres Tarus 1 Kupang Regency totaling 27 students, consisting of 15 boys and 12 girls. Data were collected through learning outcomes tests, teacher activity observations, learner activity observations, and documentations. Data analysis techniques used were quantitative and qualitative data analysis techniques. The results showed a significant increase in learning outcomes. Learning completeness increased from 18,5% in the pre-cycle to 41% in cycle I, and reached 93% in cycle II. Based on research conducted at SD Inpres Tarus 1 Kupang Regency on the use of problem based learning models assisted by wordwall media to improve the learning outcomes of Vc class students, which were analyzed through observations of students activities and competency tests and understanding of material about regional culture, the data obtained that in cycle I the score of student activity was 51,81. This score then increased in cycle II to 80,18. In addition, data from the final tests showed in increase in the percentage of students learning completeness from 64% in cycle I to 83,5% in cycle II. Thus, the problem based learning model assisted by wordwall media can be an alternative learning strategy that is effective in improving student learning outcomes in elementary school.